(Almost) everything is a Dicke model - Mapping non-superradiant correlated light-matter systems to the exactly solvable Dicke model - Schellenberger, Andreas; Schmidt, Kai Phillip (SciPost Physics Core, 2024)
We investigate classes of interacting quantum spin systems in a single-mode cavity with a Dicke coupling, as a paradigmatic example of strongly correlated light-matter systems. Coming from the limit of weak light-matter couplings and large number of matter entities, we map the relevant low-energy sector of a broad class of models in the nonsuperradiant phases onto the exactly solvable Dicke model. We apply the outcomes to the Dicke-Ising model as a paradigmatic example [1,2], in agreement with results obtained by mean-field theory [2]. We further accompany and verify our findings with finite-size calculations, using exact diagonalization and the series expansion method pcst++ [3].
CRIS-Team Scopus Importer:2024-07-19

Dynamic structure factor of the antiferromagnetic Kitaev model in large magnetic fields - Schellenberger, Andreas; Hörmann, Max; Schmidt, Kai Phillip (Physical Review B, 2022)
We investigate the dynamic structure factor of the antiferromagnetic Kitaev honeycomb model in a magnetic field by applying perturbative continuous unitary transformations about the high-field limit. One- and two-quasiparticle properties of the dressed elementary spin-flip excitations of the high-field polarized phase are calculated, which account for most of the spectral weight in the dynamic structure factor. We discuss the evolution of spectral features in these quasiparticle sectors in terms of one-quasiparticle dispersions, two-quasiparticle continua, the formation of antibound states, and quasiparticle decay. In particular, a comparably strong spectral feature above the upper edge of the upmost two-quasiparticle continuum represents three antibound states which form due to nearest-neighbor density-density interactions.
CRIS-Team Scopus Importer:2022-09-30

Series expansions in closed and open quantum many-body systems with multiple quasiparticle types - Lenke, Lea; Schellenberger, Andreas; Schmidt, Kai Phillip (Physical Review A, 2023)
The established approach of perturbative continuous unitary transformations (pCUTs) constructs effective quantum many-body Hamiltonians as perturbative series that conserve the number of one quasiparticle type. We extend the pCUT method to similarity transformations - dubbed pcst++ - allowing for multiple quasiparticle types with complex-valued energies. This enlarges the field of application to closed and open quantum many-body systems with unperturbed operators corresponding to arbitrary superimposed ladder spectra. To this end, a generalized counting operator is combined with the quasiparticle generator for open quantum systems recently introduced by Schmiedinghoff and Uhrig [G. Schmiedinghoff and G. S. Uhrig, SciPost Phys. 13, 122 (2022)2542-465310.21468/SciPostPhys.13.6.122]. The pcst++ then yields model-independent block-diagonal effective Hamiltonians and Lindbladians, allowing a linked-cluster expansion in the thermodynamic limit similar to the conventional pCUT method. We illustrate the application of the pcst++ method by discussing representative closed, open, and non-Hermitian quantum systems.
CRIS-Team Scopus Importer:2023-08-18